The Role of Self-Control on Employee Cyberloafing Behavior - HIdayana, Nugrhainy; Padli Nasution, Muhammad Irwan; Syarbani, Ahmad Muhaisin B. (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The free use of the internet in the work environment has become a common phenomenon, including in the work environment of law enforcement officers such as the Police. This can disrupt concentration and work productivity. This research aims to determine and analyze the role of self-control in the cyberloafing behavior of employees at the Simalungun Police Department using descriptive quantitative research methods. The population in this study was 557 consisting of Simalungun Police police staff employees. Meanwhile, the number of samples in this research was 85 with a sampling technique using the Sloving formula. Data collection techniques as a tool for collecting research data at research locations using observation, questionnaires, and documentation. Meanwhile, the data analysis technique used is the Outer Model, Inner Model, and parametric statistical tests with the help of the Partial Least Square (PLS-SEM) computer program to analyze the relationship between self-control variables and cyberloafing behavior. The research results show a positive relationship between self-control and cyberloafing behavior (r=0.497 and p<0.05), as evidenced by the r square inner model calculation results. The calculated t value is also 9.299, has exceeded the t value (table) of 1.96, and the significance is 0.000, namely <0.05. Therefore, it can be concluded that self-control among Simalungun Police Staff Members has a posi